2014
DOI: 10.1111/1753-0407.12157
|View full text |Cite
|
Sign up to set email alerts
|

Waist‐to‐height ratio is an appropriate index for identifying cardiometabolic risk in Chinese individuals with normal body mass index and waist circumference 腰臀比是鉴别体重指数和腰围正常的中国人群的心血管代谢风险的适宜指标

Abstract: Waist-to-height ratio might be an effective index to identify cardiometabolic risk factors in Chinese with normal BMI and WC, particularly in females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 35 publications
(78 reference statements)
2
31
0
3
Order By: Relevance
“…The beneficial effect of nutritional education interventions on abdominal obesity in pediatric populations constitutes an important finding for several reasons. First, central adiposity appears to be the predominant diagnostic criteria for MetS [38,39] and related comorbidities [40,41] as reported in the literature. Moreover, abdominal adiposity is an outcome sensitive to changes in nutrition and lifestyle [42,43], which are the main components of the evaluated education interventions.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The beneficial effect of nutritional education interventions on abdominal obesity in pediatric populations constitutes an important finding for several reasons. First, central adiposity appears to be the predominant diagnostic criteria for MetS [38,39] and related comorbidities [40,41] as reported in the literature. Moreover, abdominal adiposity is an outcome sensitive to changes in nutrition and lifestyle [42,43], which are the main components of the evaluated education interventions.…”
Section: Discussionmentioning
confidence: 86%
“…BMI has high specificity but low sensitivity to detect excess adiposity and fails to identify over a quarter of children with an excess body fat percentage [40,50,51]. Assessment of central adiposity by measuring WC, waist-to-height ratio or waist-to-hip ratio (the parameters included in our review) is thus even more important when evaluating a pediatric population [40,41]. Compared with BMI, WC is a better indicator of obesity-related health risk.…”
Section: Discussionmentioning
confidence: 99%
“…The optimal cut-off values for WHtR in the detection of cardio-metabolic risk factors were identified by receiver operating characteristic curve analysis confirming value of 0.5 as boundary of Caucasian, Asian and Central American subjects (10,11), in sub-population of ethnic South Asian adults (12), and Chinese adults (13,14).…”
Section: Introductionmentioning
confidence: 91%
“…However, a recent systematic review demonstrated that waist-to-height ratio (WHtR) is a significantly more favourable screening tool for adult metabolic risk factors than are BMI and WC (16) , and reported that compared with BMI, WC improved the discrimination of adverse cardiovascular risk outcomes by 3 % and WHtR improved discrimination by 4-5 %. As well, WHtR is able to evaluate cardiovascular risk factors and to effectively predict the incidence of metabolic syndrome in non-obese people (17)(18)(19)(20) . However, the problem is that none of these indices alone is able to distinguish subcutaneous fat from the visceral fat which is more strongly associated with metabolic abnormalities.…”
mentioning
confidence: 99%